The relationship between internet addiction and mental health problems such as depression symptoms, anxiety and insomnia before and during Covid-19 pandemic - Biedroń, Natalia; Szabat, Marta; Dąbrowski, Jan; Dębek, Karolina; Gąbka, Ilona (Journal of Education, Health and Sport, 2021)
Introduction: On the account of the Covid-19 pandemic, many governments around the world have imposed multiple restrictions on public life to prevent the spread of the coronavirus. Social disruption and forced isolation contributed to increased stress as well as increased use of the Internet. Aim of the study: The aim of the study was to investigate the influence of the Covid-19 pandemic on mental health problems, including Internet addiction, and to link Internet addiction with mental health problems such as anxiety, depression symptoms and insomnia. Material and methods: The data for the article was found using the PubMed and Google Scholar websites. Description of the state of knowledge: Internet addiction (IA) is becoming an increasingly serious problem of the modern world. The problem of Internet abuse is associated with various risk factors that are dependent on gender or family relationships, as well as mental disorders. Many studies have confirmed that the Covid-19 pandemic caused negative mental health effects, contributing to increased anxiety and depression symptoms. To reduce stress, people started using the internet more often. This compensatory mechanism can cause even more mental health problems by increasing anxiety, symptoms of depression and insomnia. Summary: Research by many scientists shows that the Covid-19 pandemic is exacerbating the mental health problems associated with IA. Research shows that during the Covid-19 pandemic, it is especially important to be able to manage stress through non-internet-related activities to help prevent IA.